0433 Does Social Media Use Before Bed Lead to Sleep Continuity Disturbance?. (25th May 2022) - Snyder, Hope; Walker, Jamie; Bell, Jessica; Egeler, Mara; Hire, Veronica; Vargas, Ivan
Abstract: Introduction: Research shows that the use of electronics before bed can negatively impact the circadian rhythm and sleep. Less is known, however, about social media use in relation to sleep continuity disturbance (i.e., insomnia). In the early months of the COVID-19 pandemic, social media use increased and updates about the pandemic were easily accessible online. It is possible that social media use before bed could introduce additional psychological stressors due to availability of negative content online and known correlations to depression and anxiety. Thus, the aim of this research was to examine how social media use before bed influenced different subtypes of insomnia during the initial months of the pandemic. Methods: 4, 138 adults (mean age = 45.8 years; 79% women) completed a national online survey during April – June 2020. Social media use before bed was measured using the first item on the Social Media Engagement questionnaire (i.e., "How often do you use social media in the 15 minutes before you go to sleep?"). Participants responded to this item based on how many days per week (range = 1-7). Sleep disturbance was assessed using a retrospective sleep diary and the Insomnia Severity Index (ISI). The sleep diary asked about sleep continuity (e.g., sleep latency, wake after sleep onset, total sleep time) during the past month. Results: Results from separate regression analyses supported that social media use before bed was positively related to greater ISI scores, b = 0.25, t = 8.0, p < 0.001. For example, those who use social media before bed every day reported greater mean ISI scores and sleep latency times (mean ISI = 9.5; SL = 37.5 minutes) compared to those who reported never using social media before bed (mean ISI = 7.7; SL = 27.9 minutes). In contrast, social media use before bed was not related to other sleep continuity variables. Conclusion: The present data supports that social media use before bed is related to insomnia symptoms, specifically difficulty with sleep initiation. These findings are significant as they may help us understand which aspects of insomnia are most vulnerable to the negative impact of online social interactions, especially during a highly stressful period, such as the COVID-19 pandemic. Support (If Any): K23HL141581 (PI: Vargas); R25HL10544 (PI: Jean-Louis); K24AG055602 (PI: Perlis)